1993
DOI: 10.1161/01.hyp.21.4.455
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin I converting enzyme gene and predisposition to high blood pressure.

Abstract: Phenotypic abnormalities of the renin-angiotensin system have been associated with the predisposition to high blood pressure. The angiotensin I converting enzyme (ACE) gene has been implicated as a candidate gene. We examined the distribution of common alleles of the ACE gene and measured circulating components of the renin-angiotensin system and urinary sodium excretion in 170 young Caucasian adults with contrasting genetic predisposition to high blood pressure. Predisposition was defined on the basis of pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
3
7

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(93 citation statements)
references
References 18 publications
9
74
3
7
Order By: Relevance
“…With respect to the ACE I\D polymorphism, the D allele displays a positive association with corresponding plasma ACE concentrations (Riget et al 1990 ;Tiret et al 1992 ;Morris et al 1994). Increases in ACE appear to result in increased Ang II formation in plasma, although this issue is still being debated (Harrap et al 1993 ;Ueda et al 1995). We suggest that increased Ang II formation, possibly combined with a higher number of receptors associated with the T allele of AT " , may lead to elevated blood pressure by synergism.…”
Section: mentioning
confidence: 69%
“…With respect to the ACE I\D polymorphism, the D allele displays a positive association with corresponding plasma ACE concentrations (Riget et al 1990 ;Tiret et al 1992 ;Morris et al 1994). Increases in ACE appear to result in increased Ang II formation in plasma, although this issue is still being debated (Harrap et al 1993 ;Ueda et al 1995). We suggest that increased Ang II formation, possibly combined with a higher number of receptors associated with the T allele of AT " , may lead to elevated blood pressure by synergism.…”
Section: mentioning
confidence: 69%
“…However, Schmidt et al, 25 studying Dutch parental couples who both had either high or low blood pressure and their offspring, found that allele frequencies were similar in parents with high and low blood pressure and in their offspring. Also, Harrap et al 26 could find no evidence that in a group of whites selected from the general population, the ACE gene was associated with genetic predisposition to high blood pressure. Interestingly, in Japanese patients with essential hypertension, the D allele was associated with early onset of hypertension and left ventricular hypertrophy, although blood pressure levels and the severity of damage to other organs were unaltered.…”
Section: Discussionmentioning
confidence: 96%
“…Various reports described the D allele as a risk factor for essential hypertension in various populations 6,7 whereas other studies disagree with that hypothesis. [8][9][10][11][12][13] Our work is, to our knowledge, the first one to be done in a Mediterranean population, and reveals no association between the I/D polymorphism and BP (Table 2). When we tested the serum activity of ACE in all of the individuals (fifth quintyl and first quintyl groups) it showed significantly higher values in individuals with more D alleles (DDϾDIϾII).…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3] The D allele was reported to be a risk factor for several cardiovascular diseases including myocardial infarction, left ventricular hypertrophy and essential hypertension in some populations under study, 4-7 but could not later be proven in others. [8][9][10][11][12][13] To our knowledge there is no evidence of any genetic study of ACE performed in a Mediterranean population.…”
Section: Introductionmentioning
confidence: 99%